The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1073/pnas.89.18.8671
|View full text |Cite
|
Sign up to set email alerts
|

A membrane-based force generation mechanism in auditory sensory cells.

Abstract: Auditory outer hair cells can elongate and shorten at acoustic frequencies in response to changes ofplasma membrane potential. We show that this fast bidirectional contractile activity consists of an electromechanical transduction process that occurs at the lateral plasma membrane and can be activated and analyzed independently in small membrane patches inside a patch electrode. Bidirectional forces are generated by increases and decreases in membrane area in response to hyperpolarization and depolarization, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
211
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(229 citation statements)
references
References 32 publications
(45 reference statements)
17
211
1
Order By: Relevance
“…Kalinec et al (1992) reported that the cytoplasmic structure was disrupted by the injection of trypsin into the OHC; however, the electromotility of the OHC, indicating the activity of prestin, was not diminished. Moreover, it has recently been reported that the voltage-dependent nonlinear capacitance, which is thought to indicate the motor activity of prestin, was measured from prestin-transfected human embryonic kidney cells despite trypsin being injected into the cells (Dong and Iwasa 2004).…”
Section: Membrane Preparation Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Kalinec et al (1992) reported that the cytoplasmic structure was disrupted by the injection of trypsin into the OHC; however, the electromotility of the OHC, indicating the activity of prestin, was not diminished. Moreover, it has recently been reported that the voltage-dependent nonlinear capacitance, which is thought to indicate the motor activity of prestin, was measured from prestin-transfected human embryonic kidney cells despite trypsin being injected into the cells (Dong and Iwasa 2004).…”
Section: Membrane Preparation Processmentioning
confidence: 99%
“…Previous morphological studies of OHCs using EM and AFM revealed the lateral membrane of OHCs to be densely covered with particles approximately 10 nm in diameter (Arima et al 1991;Forge 1991;Kalinec et al 1992: Souter et al 1995Le Grimellec et al 2002), these particles being believed to be motor protein. Two membrane proteins, i.e., a fructose transporter, GLUT-5 (Géléoc et al 1999), and an anion/ sulfate transporter, prestin (Zheng et al 2000), were proposed to be this motor.…”
Section: Imaging Of Membrane Protein Prestinmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prestin appears to be unable to diffuse from the lateral wall to the basal pole, even upon degradation of the cytoskeleton (Takahashi and Santos-Sacchi 2001). Likewise, receptors and ion channels in the basal pole do not migrate to the lateral wall (Kalinec et al 1992;Zhang and Kalinec 2002). Therefore, some other mechanism organizes and preserves the molecular composition of these membrane areas, and it is conceivable that the OHC actively maintains a distinct lipid composition in each of the three regions.…”
Section: Introductionmentioning
confidence: 99%
“…In OHCs, however, the basolateral plasma membrane itself is further divided into two structurally and functionally different regions. The lateral region lacks voltage-gated channels but holds thousands of integral membrane proteins ( 7000/lm 2 ) (Gulley and Reese 1977;Forge 1991;Kalinec et al 1992;Huang and Santos±Sacchi 1993;Kalinec and Kachar 1995;Souter et al 1995;Holley 1996;Santos±Sacchi et al 1997). These integral membrane proteins are currently associated with the motor molecules responsible for the reversible and very fast changes in cell length known as OHC electromotility (Geleoc et al 1999;Zheng et al 2000;Belyantseva et al 2000;Oliver et al 2001).…”
Section: Introductionmentioning
confidence: 99%